2007
DOI: 10.3748/wjg.v13.45.6003
|View full text |Cite
|
Sign up to set email alerts
|

NAT2*6A, a haplotype of the N-acetyltransferase 2 gene, is an important biomarker for risk of anti-tuberculosis drug-induced hepatotoxicity in Japanese patients with tuberculosis

Abstract: The present study shows that NAT2 is one of the determinants of anti-TB drug-induced hepatotoxicity. Moreover, the haplotypes, NAT2 4 and NAT2 6A, are useful new biomarkers for predicting anti-TB drug-induced hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 23 publications
4
44
0
1
Order By: Relevance
“…Expected genotype frequencies were calculated from respective single allele frequencies and were consistent with Hardy Weinberg equilibrium. Table 1 describes the allelic distribution of the four variants of NAT-2 that had the strongest impact on the acetylation profile in the Buenos Aires population and in different populations from various regions of Europe [1], Africa [1,12], Asia [1,6,9] and America [1,7 ,9, 13]. Our study group consisted of an admixture of ethnic groups with European (mainly from Spain, Italy and, to a lesser extent, from Germany and other countries of Eastern Europe), and Native American ancestries.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expected genotype frequencies were calculated from respective single allele frequencies and were consistent with Hardy Weinberg equilibrium. Table 1 describes the allelic distribution of the four variants of NAT-2 that had the strongest impact on the acetylation profile in the Buenos Aires population and in different populations from various regions of Europe [1], Africa [1,12], Asia [1,6,9] and America [1,7 ,9, 13]. Our study group consisted of an admixture of ethnic groups with European (mainly from Spain, Italy and, to a lesser extent, from Germany and other countries of Eastern Europe), and Native American ancestries.…”
Section: Methodsmentioning
confidence: 99%
“…The major alleles groups associated with decreased enzyme activity due to amino acid changes and, therefore, a slow acetylator phenotype, are NAT-2*5, NAT-2*6, NAT-2*7 and NAT-2*14 [4]; in several surveys homozygous wild type alleles at all four loci that have no variations are called RA and are represented as NAT-2*4 [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, fast acetylation of AcHZ and Hz in NAT2 rapid acetylators should theoretically form DiAcHZ efficiently and therefore reducing the oxidative metabolites accumulation from AcHZ. In fact, several studies found an increased risk in slow versus fast acetylators through genetically determined phenotype (Higuchi et al 2007). However, there are conflicting data on whether CYP2E1 genotypes do or do not increase the risk of isoniazid-induced (Cho et al 2007).…”
Section: Clinical Pharmacogenetics and Potential Applicationsmentioning
confidence: 99%